Effects of acupuncture on musculoskeletal pain: an evidence map - Ang, Lin; Song, Eunhye; Choi, Tae-Young; Jun, Ji Hee; Lee, Boram; Yim, Mi Hong; Lee, Hye Won; Lee, Myeong Soo (Frontiers in Medicine, 2025)
BackgroundMusculoskeletal pain is a leading cause of disability and reduced quality of life worldwide. Given the growing interest in complementary and alternative therapies, acupuncture has been widely explored as a potential treatment for alleviating musculoskeletal pain. This evidence map aimed to identify, describe, and summarize the current available evidence about acupuncture interventions on musculoskeletal pain.MethodsFor this map, searches were conducted in PubMed, Embase, Cochrane Library, Allied and Complementary Medicine Database (AMED), Web of Science, and Epistemonikos to identify systematic reviews (SRs) with meta-analysis published up to 23 August 2024. Included SRs were independently assessed for eligibility in pairs. The data from the eligible SRs were extracted and evaluated for methodological quality using AMSTAR 2. The findings were tabulated and mapped using bubble plots.ResultsA total of 111 SRs fulfilled the eligibility criteria and were included in this evidence map. All of the SRs included manual acupuncture or electroacupuncture. Comparators included in SRs involved active comparators, inactive comparators, sham acupuncture, and no intervention. The included 111 SRs were categorized into 35 musculoskeletal pain conditions. The short-term effects of acupuncture showed a positive effect across most comparators in major musculoskeletal pain. All included SRs were rated low or critically low in terms of methodological quality.ConclusionThis evidence map demonstrated that acupuncture has favorable effects on major musculoskeletal disorders. Further improvements in the quality of evidence should be prioritized and more clinical trials on the acupuncture for treating musculoskeletal pain are needed.